Effects of hamstrings-to-quadriceps ratio and the lower extremity performance during single-leg drop jump in female basketball players: A pilot study - Hsiao, H. W.; Tseng, P. C.; Lee, H. J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Lower limb injuries commonly occur in female basketball players due to basketball having a unilaterally dominant characteristic, which may lead to an imbalance in the strength and reaction of the lower limbs. In past studies, the effect of knee flexor and extensor strength differences in the lower limbs has been extensively discussed to the risk of injury. Additionally, lower limb strength and landing style significantly influence jumping performance. This may increase the incidence of non-contact injuries while landing and jumping. In contrast, the reactive strength index (RSI) is reliable for evaluating plyometric performance and examining both jump and landing capability. However, the relationships between the hamstrings-to-quadriceps (H/Q) ratio value and sports performance in both legs have yet to be thoroughly investigated. Therefore, this study aimed to examine the differences between single-leg drop jump (SLDJ) performance and H/Q ratio in female basketball players.